2011
DOI: 10.1111/j.1601-0825.2011.01843.x
|View full text |Cite
|
Sign up to set email alerts
|

MCP‐1 and CCR2 gene variants in oral squamous cell carcinoma

Abstract: We can suggest that the G allele of MCP-1 and 64I allele of CCR2 may be risk factors for OSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Degerli et al (2005) studied the CCR5-delta32 allele distribution and its relationship with breast, laryngeal, thyroid, and brain carcinomas in a Turkish population, which did not reveal any statistically significant relationships. In our previous studies, we found that the MCP-1 A2518G and CCR2-V64I genotypes were risk factors for endometrial (Attar et al, 2010), bladder (Narter et al, 2010), and oral cancer (Bektas-Kayhan et al, 2012). To the best of our knowledge, only two studies have investigated CCR5 variants with respect to the risk of oral cancer development.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Degerli et al (2005) studied the CCR5-delta32 allele distribution and its relationship with breast, laryngeal, thyroid, and brain carcinomas in a Turkish population, which did not reveal any statistically significant relationships. In our previous studies, we found that the MCP-1 A2518G and CCR2-V64I genotypes were risk factors for endometrial (Attar et al, 2010), bladder (Narter et al, 2010), and oral cancer (Bektas-Kayhan et al, 2012). To the best of our knowledge, only two studies have investigated CCR5 variants with respect to the risk of oral cancer development.…”
Section: Discussionmentioning
confidence: 97%
“…Epidemiological studies have suggested that OSCC is a multifactorial disease that can be mediated by both environmental factors, such as alcohol and tobacco consumption, and genetic factors (Weng et al, 2010;Bektas-Kayhan et al, 2012). In parallel with these studies, we found that CCR5 59029 G+ genotypes (GG + AG), gender, smoking, alcohol consumption, and age were all associated with OSCC risk in univariate analyses; however, only CCR5 59029 G+ genotypes and alcohol consumption were associated with the disease in multivariate logistic regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…After HWE test, 3 articles (Saenz-Lopez et al, 2008;Attar et al, 2010;Gu et al, 2011) were deviated from HWE. Thus, a total of 11 case-control studies were extracted (VazquezLavista et al, 2009;Narter et al, 2010;Yang et al, 2010;Yeh et al, 2010;Chen et al, 2011;Kruszyna et al, 2011;Kucukgergin et al, 2012a;Kucukgergin et al, 2012b;Bektas-Kayhan et al, 2012;Singh et al, 2012;Wu et al, 2013). The characteristics of each case-control study are listed in Table 1.…”
Section: Study Inclusion and Characteristicsmentioning
confidence: 99%
“…Also, another group demonstrated that mutation of MCP-1 gene, which encodes CCR2 ligands, increased the expression of MCP-1 resulting in elevated CCR2 activity which could increase the risk for developing oral squamous carcinoma [23]. The authors predicted that MCP-1 and CCR2 could be used as genetic markers for diagnosis of oral carcinoma squamous [23].…”
Section: Chemokine Receptors As Biomarkers In Head and Neck Squamous mentioning
confidence: 99%
“…Also, another group demonstrated that mutation of MCP-1 gene, which encodes CCR2 ligands, increased the expression of MCP-1 resulting in elevated CCR2 activity which could increase the risk for developing oral squamous carcinoma [23]. The authors predicted that MCP-1 and CCR2 could be used as genetic markers for diagnosis of oral carcinoma squamous [23].Another CC chemokine receptor, i.e., CCR7, which plays a critical role in the migration of activated dendritic cells to regional lymph nodes, was also found elevated in HNSCC tumor tissues compared with paraneoplastic tissues and the elevated expression of CCR7 was correlated with lymph metastasis and tumor tissue differentiation status [21]. Another study evaluated the expression of CCR7 in primary and metastatic tumor cell lines and biopsies from both primary and metastatic lesions, and it was found that CCR7 expression was elevated in metastatic cells and tissues [24].…”
mentioning
confidence: 99%